An effect of finite reservoir size on pressure gradient generation in a pinched injection sample plug generation in cross design electroosmotic microfluidic device - P. Chimsiri (2020)
© Published under licence by IOP Publishing Ltd. In performing microfluidic electrophoresis, sample loading must be prioritized since the shape of the initial sample plug injected into the separation channel immensely influences the electrophoretic separation efficiency. Non-zero pressure gradient due to different liquid level in finite size reservoirs is generated as a result of continuous electroosmotic flow (EOF) pumping, resulting in undesired parabolic pressure profile both in the same and opposite direction of sample propagation. This issue could be alleviated by fabricating larger reservoirs which can maintain the liquid level due to gradual volume changing as time elapses. This work presents experimental and numerical study on effect of 3.5-8.0 mm reservoir size on Rhodamine B plug flow generation from pinched injection sample loading method in cross design microfluidic device. COMSOL Multiphysics AC/DC module was used in calculating electric field distribution from desired applied voltages. The shapes of the injected sample plugs in the beginning of separation step were studied by varying the time of injection step. The experimental result shows that long-tailed sample plug and pressure profiles were generated when the injection time is 2 minutes or more. For the 8 mm diameter reservoirs, the flow profile illustrates pure EOF plug flow when the injection time does not exceed 1.5 minutes. This implies pressure gradient is virtually disappeared. The result of this study will be later applied for protein transferrin electrophoretic separation.